К вопросу об и.-е. *s после i, u в литовском языке - Karaliūnas, Simas (Baltistica, 1966)
CONCERNING THE IE *s AFTER i, и IN THE LITHUANIAN LANGUAGEThe analysis of Lithuanian language material allows us to assume that the IE *s following i, и has changed into the phoneme š in words isolated regarding their derivation (type maĩšas). When the phonetical change of the IE *s was to have affected the morphological or derivative characteristics of a word, the phoneme s which followed i, и remained unchanged. In the words of the type saũsas the phoneme s, for certain reasons (probably, on account of vowel interchange), might have become associated with s that occurred in suffixes (cf. *gaũ-sas ≤ gausus beside gáu-ti). Besides, it is possible that the IE *s did not develop into š before some consonants. The reflex of the IE *s after i, u, r, k and that of the IE palatal *k̑ were the phoneme š; consequently, we may assume that these changes in Lithuanian were processes structurally linked together.
Keywords: konsonantizmas; konsonantizmo raida; istorinė gramatika